Analysis on the impact of recycled ceramic waste, fiber format, and manufacturing techniques on polymer composite properties. (1st December 2022) - Sakthi Balan, G; Prakash, B; Aravind Raj, S; Karthik, S; Mohan Kumar, V
Abstract: Dumping of construction waste is a growing issue in current situation and recycling and reusing are the suitable solutions for solving it. This effort aims to recycle and reuse of ceramic construction waste. This work examines the effects of inclusion of waste tile powder, change in the glass fiber form which was used as a reinforcement, and method of manufacturing method the polymer composite on the properties of the composite. Normal glass-reinforced polymer composites have good tensile, flexural, and toughness properties. The three forms of glass fibers used for the study includes, chopped fiber mat, glass fiber mesh, and woven glass fiber. Fillers are added to improve hardness and tribology related attributes. Composite fabrication was carried out by conventional hand layup, room temperature compression molding, and hot compression molding process. The goal is to harden the composite without reducing the tensile strength of the composite. ASTM D3039, ASTM D2240, and ASTM D570–98 procedures were adapted for measuring tensile, hardness and water intake properties respectively. Characterization was done through SEM image analysis. A result of 160.21 MPa tensile strength, Shore D hardness value of 96.7, and water absorption of 0.71 percent after 24 h of testing was recorded. Adding waste tile powder to the polymer composite increases its hardness and reduces surface defects without affecting tensile properties. Fiber form and manufacturing method also affect the output to some extent. The effect of water absorption on the hardness property of the composite was checked and found to be negligible which makes it durable and reliable to be used in moist environments. This composite can be used in automotive parts, moist environment, window and door frames, and in electrical panels.